-4(6y-5)-y=-2(y-2)

Simple and best practice solution for -4(6y-5)-y=-2(y-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(6y-5)-y=-2(y-2) equation:


Simplifying
-4(6y + -5) + -1y = -2(y + -2)

Reorder the terms:
-4(-5 + 6y) + -1y = -2(y + -2)
(-5 * -4 + 6y * -4) + -1y = -2(y + -2)
(20 + -24y) + -1y = -2(y + -2)

Combine like terms: -24y + -1y = -25y
20 + -25y = -2(y + -2)

Reorder the terms:
20 + -25y = -2(-2 + y)
20 + -25y = (-2 * -2 + y * -2)
20 + -25y = (4 + -2y)

Solving
20 + -25y = 4 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
20 + -25y + 2y = 4 + -2y + 2y

Combine like terms: -25y + 2y = -23y
20 + -23y = 4 + -2y + 2y

Combine like terms: -2y + 2y = 0
20 + -23y = 4 + 0
20 + -23y = 4

Add '-20' to each side of the equation.
20 + -20 + -23y = 4 + -20

Combine like terms: 20 + -20 = 0
0 + -23y = 4 + -20
-23y = 4 + -20

Combine like terms: 4 + -20 = -16
-23y = -16

Divide each side by '-23'.
y = 0.6956521739

Simplifying
y = 0.6956521739

See similar equations:

| 3p+13=-29 | | 8x-3=2(x+15) | | 1/10(x+3)=1/4(2-x) | | 4m-3+7m=30 | | 2(x-5)+3=11 | | x+0.8=0.4(x+5) | | 10+2x=50 | | (7x+9)=(6+10x) | | 4x+1.3=6x-1.1 | | 2x-72+x-15=11 | | 2a^2-3a+5=0 | | 2x-1080=2x-11 | | 4(x-4)+2x=6(x+5)-46 | | 8(x-3)=4 | | x-9=-3x-9 | | 2x-72+x-15=2x-11 | | -7(x-4)=21 | | x-15=2x-72 | | 10-2x=50 | | x/4+4/5=5/12 | | 7x-3+3x=9 | | 5(x+7)=4(x-6)+x | | 7x-3+9=3x | | 7x-3=3x | | 6(-7)+x=7(x-7)+7 | | 2x+11=19-2x | | 20(x+3)=4(15+5x) | | 2x-5/8+x=2x+5/2+2 | | -3(2m-9)+7(m-4)=12-9 | | x/2-4=2 | | -6x-x=0 | | x^4-3x^2-10= |

Equations solver categories